VCP : VMware certified professional on vSphere 4 study guide - Perry, Brian, 1966-; Huss, Chris, 1972-; Fields, Jeantet, 1973- (Indianapolis, Ind. : Wiley Technology Publishing, 2010)
'VMware vSphere 4 virtualization certification-here's how to prepare for the exam! VMware's vSphere 4 is the latest offering from this leading virtualization software provider. With today's emphasis on going green and cutting costs, virtualization of IT infrastructures is a hot topic. What better way to show the marketplace your virtualization expertise than with a VMware Certified Professional on vSphere 4 certification? This in-depth study guide covers all exam objectives, thoroughly preparing you with challenging review questions, real-world scenarios, hands-on exercises, and more. VMware's vSphere 4 is the latest offering from VMware, the leading virtualization software provider on the market. Prepares you for the VMware Certified Professional (VCP) on vSphere 4 (VCP-410) certification exam, with complete coverage of all exam objectives. Guides you through such topics as planning, installing, and upgrading ESX/ESXi; configuring ESX/ESXi networking and storage; installing and configuring vCenter Server; deploying and managing virtual machines; and more. Reinforces your preparation with challenging review questions, hands-on exercises, and real-world scenarios. Includes a CD with Sybex test engine, electronic flashcards, and practice exams. Make sure you're ready for VMware's VCP certification exam with this packed study guide.'--
Book is accompanied by 1 CD, entitled.' VCP : VMware certified professional on vSphere 4 study guide' bearing the same call number and available at Bahagian Koleksi Media
Keywords: VMware; Electronic data processing personnel -- Certification; Virtual computer systems -- Examinations -- Study guides